2003
DOI: 10.1021/jp0308312
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Salts, Acids, and Phenols on the Hydrogen-Bonding Structure of Water−Ethanol Mixtures

Abstract: The effects of salts, acids, and phenols on the hydrogen-bonding structure of water in 20% (v/v) EtOH−H2O solution were investigated on the basis of 1H NMR chemical shifts of the OH of water and ethanol. It was found that many salts caused structure breaking of water while a few metal salts, such as MgCl2 and KF, had a strengthening effect. The OH proton chemical shifts caused by the presence of alkali-metal and alkaline-earth-metal ions or anions (halides, NO3 -, ClO4 -, SO4 2-) from strong acids were related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 32 publications
1
67
1
1
Order By: Relevance
“…[41] The pK a of DPPH has been reported to be 8.59. [11,42] The weakly acidic phenols (1 with pK a = 7.34 [43] or 7.62 [44,45] and 2 with pK a = 8.70 [43] ) give rise to fairly strong bases 3 and 4. Because only 3 (not 4) could be obtained in the solid state, denoted below by subscript (s), the reaction with DPPH was performed only with this phenol.…”
Section: The Reaction Of Dpph With the Sodium Aroxide 3 In The Presenmentioning
confidence: 99%
“…[41] The pK a of DPPH has been reported to be 8.59. [11,42] The weakly acidic phenols (1 with pK a = 7.34 [43] or 7.62 [44,45] and 2 with pK a = 8.70 [43] ) give rise to fairly strong bases 3 and 4. Because only 3 (not 4) could be obtained in the solid state, denoted below by subscript (s), the reaction with DPPH was performed only with this phenol.…”
Section: The Reaction Of Dpph With the Sodium Aroxide 3 In The Presenmentioning
confidence: 99%
“…These results are probably based on the difference of anion effects; we have observed that anions with the larger crystal ionic radius cause the larger effects on the chemical shifts of water towards upper-field, as Cl À < NO 3 À < Br À < I À % ClO 4 À , in 2.0% 38 and 20 vol % EtOH-H 2 O solutions. 39 The 1 H NMR chemical shift can identify the presence of strong acids in reverse micelle systems, as well as in bulk water or bulk H 2 O-EtOH mixed solution. …”
Section: à3mentioning
confidence: 99%
“…NMR is a sensitive probe used for investigation of the electronic structure and intermolecular interactions, in particular hydrogen bonding interactions [4][5][6][7]. NMR of the 1-butyl-3-methylimidazolium tetrafluoroborate (BmimBF 4 ) and 1-butyl-3-methylimidazolium hexafluorophosphate (BmimPF 6 ) have been studied by Suarez et al, where they attributed the high chemical shifts of imidazolium protons to a hydrogen bond with the anions [8].…”
Section: Introductionmentioning
confidence: 99%
“…NMR of the 1-butyl-3-methylimidazolium tetrafluoroborate (BmimBF 4 ) and 1-butyl-3-methylimidazolium hexafluorophosphate (BmimPF 6 ) have been studied by Suarez et al, where they attributed the high chemical shifts of imidazolium protons to a hydrogen bond with the anions [8]. Holbrey and Seddon also used 1 H NMR to probe hydrogen bonding in the liquid phase for 1-alkyl-3-methylimidazolium tetrafluoroborate salts (C n mimBF 4 , n = 0-18); however, they found no significant H-bonding to anion, since the chemical shift values of…”
Section: Introductionmentioning
confidence: 99%